Pendidikan Agama Islam Dalam Keluarga: Perspektif Manuskrip H. Ismail Arsyad Kubu (1956) - Sofyan, Anas; Mahrus, Erwin (IAIN Pontianak, 2024)
This research aims to analyze Islamic religious education in the family based on the perspective of H. Ismail Arsyad Kubu's manuscript. This text contains guidelines and values taught in the family context to shape children's character and faith. The method used in research is literature with a qualitative approach with a descriptive method, namely a problem solving method by carefully reading ideas or thoughts and analyzing texts, emphasizing the principles of religious education, the values instilled and recommended. teaching strategies. in the script. The research results show that H. Ismail Arsyad Kubu's text emphasizes the importance of the role of parents as the main role models in religious education. Parents are expected to be actively involved in providing understanding of religion through various approaches, such as stories, discussions and daily worship practices. Apart from that, this text also highlights the importance of learning that is contextual and appropriate to children's psychological development. Religious education in the family, according to this text, must be carried out with love and patience, and adapted to the conditions and situation of each family. These findings provide an important contribution to the development of a model of Islamic religious education in the family that is more effective, relevant and adaptive to changing times. This study also offers valuable historical insight into the practice of religious education in families in the past, which is still relevant to apply today.